GAMBARAN SOSIAL BUDAYA TERHADAP DIABETES MELITUS PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS GUNUNGTUA KECAMATAN PADANG BOLAK KABUPATEN PADANG LA WAS UTARA TAHUN 2014 - fitri hairani; Alam Bakti Keloko; Namora lumongga (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Socio-cultural overview of diabetes mellitus in society is to describe the way of life the people who appear on behavioral manifestations diabtes mellitus patients. This research is research that is descriptive with quantitative approach which aims to determine the socio-cultural overview of diabetes mellitus in society in Puskesmas Gunung Tua, Padang Bolak District, Padang Lawas Utara Sub -district. The population in this study were all patients with diabetes mellitus who went to the puskesmas Gunungtua as many as 54 people. The sample in this study the entire amount of people with diabetes mellitus are 54 people. The analysis used was a univariate analysis. The result of this research is the knowledge of the respondents in setting the pattern of eating is moderate namely 21 people (38,9), and bad 19 people ( 35,2 ) , attitudes toward diet which is currently 34 people ( 63,0 ) and good 13 people ( 24.1 ) , the action of the diet is good that 32 people ( 59.3 ) and bad 22 people ( 40.7 .) Knowledge of physical activity is good that 23 people ( 42,6 ) and moderate 19 people ( 35,2 ) , attitudes toward physical activity is moderate at 41 people ( 75,9) and good 8 people ( 14,8 ) , action against activities physical is good that 50 people ( 92.6 ) and bad that 4 people ( 7,14 ) .